Super Scientists - Snedden, Robert; di Baldo, Fabrizio (Essex Miles Kelly Publishing Ltd, 2023)
This brilliant book uncovers every fascinating fact you could possibly want to know about some scientists and their work. From simple questions such as 'What's happening to the climate?', to the more obscure ponderings of 'Where can you find a space garden?', your curious young learner will have 100% reading satisfaction
Famous People
Keywords: inventors